2018
DOI: 10.1371/journal.pone.0201829
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota influence the development of the brain and behaviors in C57BL/6J mice

Abstract: We investigated the contributions of commensal bacteria to brain structural maturation by magnetic resonance imaging and behavioral tests in four and 12 weeks old C57BL/6J specific pathogen free (SPF) and germ free (GF) mice. SPF mice had increased volumes and fractional anisotropy in major gray and white matter areas and higher levels of myelination in total brain, major white and grey matter structures at either four or 12 weeks of age, demonstrating better brain maturation and organization. In open field te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 109 publications
(128 reference statements)
9
99
2
Order By: Relevance
“…MPF mapping is a validated biomarker of myelination in neural tissues. The method has high resolution, fast and independent of directional tissue organization, and therefore is uniquely suited to assess myelination in gray matter structures (Khodanovich et al, 2017; Lu et al, 2018; Yarnykh et al, 2015). MPF provided complementary information to diffusion tensor imaging in white and gray matter in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPF mapping is a validated biomarker of myelination in neural tissues. The method has high resolution, fast and independent of directional tissue organization, and therefore is uniquely suited to assess myelination in gray matter structures (Khodanovich et al, 2017; Lu et al, 2018; Yarnykh et al, 2015). MPF provided complementary information to diffusion tensor imaging in white and gray matter in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The publicly available MRMNeAt atlas database was used, containing 10 individually labeled C57BL/6 J in vivo mouse brains. Twenty‐one white and gray matter structures from the atlas were mapped for each mouse brain (Lu et al, 2018). Volumes of individual anatomical areas and values of MPF were compared between control and IH groups.…”
Section: Methodsmentioning
confidence: 99%
“…16,17 A newer quantitative MRI method, fast macromolecular proton fraction (MPF) mapping, 18,19 has been recently adapted to fetal brain applications. 20,21 MPF has been histologically validated as a myelin biomarker in animal models [22][23][24][25] and has shown the capability to quantify myelin damage in clinical studies of multiple sclerosis 26,27 and mild traumatic brain injury. 28 In the recent normal fetal 20 and pediatric 29 brain studies, MPF maps demonstrated close quantitative agreement with spatiotemporal trajectories of myelin development.…”
mentioning
confidence: 99%
“…Ethics statement. All zebrafish experiments were approved by the University of Oregon Institutional Animal Care and Use Committee (protocols 18-08 and [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%
“…15 Mice raised germ-free (GF) or with an abnormal microbiota exhibit impaired social behavior, which is correlated with microbial modulation of neuronal gene expression, neurotransmitter levels, brain maturation, and myelination. [16][17][18][19][20][21][22] Host-associated microbes influence social behavior across taxa. For example, the Drosophila melanogaster microbiota promotes social preference through serotonergic signaling.…”
Section: Introductionmentioning
confidence: 99%